Distribution-neutral Welfare Ranking-Extending Pareto Principle - Sugata Marjit; Sandip Sarkar (Center for Economic Studies and ifo Institute (CESifo), 2017)
The well known Pareto criterion used in the context of efficiency and welfare has to do with absolute changes whereas in every domain of economic behaviour inequality or relative changes has become a major concern. We propose an inequality-preserving or distribution neutral Pareto criterion-the strong Pareto superior or SPS allocation which preserves the initial distribution and makes everyone better off. Our main result is that whenever there is a gain in the aggregate value of the relevant attribute, there exists a unique counterfactual allocation which is SPS.
Keywords: A10; 330; Pareto superiority; strong Pareto superiority; inequality